Studies on pharmaceutical ethnobotany in the regions of L'Alt Empordà and Les Guilleries (Catalonia, Iberian Peninsula). - Bonet, M a; Parada, M; Selga, A; Vallès, J (Journal of ethnopharmacology, 1999)
An ethnobotanical survey was carried out in two regions (L'Alt Emporda and Les Guilleries), situated in North East Catalonia (Iberian Peninsula), with an approximate area of 800 km2 and a population of 68000. Through interviews with 73 people, data was obtained on the medicinal uses of 220 species. The most important findings are presented here concerning the ethnopharmacology of those areas. One hundred and ninty four unreported or uncommon uses corresponding to 101 plant species were detected.
Keywords: Catalonia; Ethnobotany; Folk medicine; Medicinal plants; Quantitative ethnobotany